BELAJAR ASYIK DAN BERMAKNA: INTEGRASI GAMIFIKASI DALAM PEMBELAJARAN KONTEKSTUAL DI SEKOLAH DASAR - Hayati, Rahmi; Karim, Asrul; Kartika, Yessi; Fachrurazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the process and impact of gamification integration in contextual learning in elementary schools as a strategy to create a fun and meaningful learning experience. The background of this study is based on the fact that conventional learning in elementary schools is still monotonous, less contextual, and minimal active student involvement. The gamification approach that adopts game elements, such as points, challenges, and levels, is combined with students' real-life contexts to increase motivation and conceptual understanding. This study uses a descriptive qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The subjects of the study included teachers, fourth grade students, principals, and parents at an elementary school that has implemented learning innovations. The results of the study indicate that contextual gamification integration can increase student involvement, strengthen intrinsic motivation, and create an active and enjoyable learning atmosphere. Teachers play an important role in designing learning that is balanced between cognitive and affective aspects. Despite facing technical and planning challenges, teachers can overcome them through reflection and adaptive strategies. In conclusion, gamification in contextual learning is an effective and relevant approach to realizing learning that touches the intellectual and emotional aspects of students in elementary schools.